Delirium in Australian Hospitals: A Prospective Study. (12th September 2013) - Travers, C.; Byrne, G. J.; Pachana, N. A.; Klein, K.; Gray, L.
Abstract : Objectives . Australian data regarding delirium in older hospitalized patients are limited. Hence, this study aimed to determine the prevalence and incidence of delirium among older patients admitted to Australian hospitals and assess associated outcomes. Method . A prospective observational study (n = 493 ) of patients aged ≥70 years admitted to four Australian hospitals was undertaken. Trained research nurses completed comprehensive geriatric assessments using standardized instruments including the Confusion Assessment Method to assess for delirium. Nurses also visited the wards daily to assess for incident delirium and other adverse outcomes. Diagnoses of dementia and delirium were established through case reviews by independent physicians. Results . Overall, 9.7% of patients had delirium at admission and a further 7.6% developed delirium during the hospital stay. Dementia was the most important predictor of delirium at (OR = 3.18, 95% CI: 1.65–6.14) and during the admission (OR = 4.82 ; 95% CI: 2.19–10.62). Delirium at and during the admission predicted increased in-hospital mortality (OR = 5.19, 95% CI: 1.27–21.24; OR = 31.07, 95% CI: 9.30–103.78). Conclusion. These Australian data confirm that delirium is a common and serious condition among older hospital patients. Hospital clinicians should maintain a high index of suspicion for delirium in older patients.